Pengambilan Keputusan Strategis Pemasaran di Perguruan Tinggi dengan menggunakan Analytics Hierarchy Process (AHP) - Arie Tunggal; Setia Budi (Jurnal Teknik Informatika dan Sistem Informasi, 2020)
In marketing strategies, it is very important to consider various variables in decision making. With intense competition in higher education, it is important to determine a more appropriate and effective marketing strategy to get prospective students. For this reason, it is necessary to investigate what factors influence prospective students in determining tertiary institutions. This study reveals that the most influencing factors for prospective students in determining academic institutions are the ease of getting a job after graduation, followed by some other supporting factors, such as: scholarships, campus reputation, spiritual activities, and campus lifestyle.